2018
DOI: 10.1177/0956797618774526
|View full text |Cite
|
Sign up to set email alerts
|

The Common Time Course of Memory Processes Revealed

Abstract: Magnetoencephalography (MEG) was used to compare memory processes in two experiments, one involving recognition of word pairs and the other involving recall of newly learned arithmetic facts. A combination of hidden semi-Markov models and multivariate pattern analysis was used to locate brief "bumps" in the sensor data that marked the onset of different stages of cognitive processing. These bumps identified a separation between a retrieval stage that identified relevant information in memory and a decision sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…In combination with the interpretation of the other stages, and given that it is longer for more difficult associations (fan-2 pairs) and foils, this stage was interpreted as a memory retrieval stage. This was later corroborated by an HsMM-MVPA analysis of a MEG dataset of the same task, which showed hippocampal and prefrontal activation during this stage (Anderson et al 2018;Borst et al 2016).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…In combination with the interpretation of the other stages, and given that it is longer for more difficult associations (fan-2 pairs) and foils, this stage was interpreted as a memory retrieval stage. This was later corroborated by an HsMM-MVPA analysis of a MEG dataset of the same task, which showed hippocampal and prefrontal activation during this stage (Anderson et al 2018;Borst et al 2016).…”
Section: Resultsmentioning
confidence: 58%
“…For targets and re-paired foils, HsMMs with 1-8 bumps were estimated. LOOCV showed a log-likelihood increase up to 6 bumps, but it was argued in Anderson et al (2016) that the 5-bump accounted better for the data (see also Anderson et al 2018 for a similar analysis and conclusion based on MEG data). We will therefore use a 5-bump HsMM for the current analysis; this model is shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, when it was applied to EEG data from the classic Sternberg task, five stages were identified: 1) pre-attention, 2) encoding, 3) memory retrieval, 4) decision, and 5) response (Anderson, Zhang, Borst, & Walsh, 2016). The HsMM-MVPA method has been proved to be a versatile method for detecting processing stages in a range of tasks (Anderson et al, 2018;Borst & Anderson, 2015;Portoles, Borst, & van Vugt, 2018;Walsh, Gunzelmann, & Anderson, 2017;Zhang, Borst, Kass, & Anderson, 2017;Zhang, van Vugt, Borst, & Anderson, 2018;Zhang, Walsh, & Anderson, 2017. At the same time, the interpretation of discovered stages remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of each stage is defined as a multivariate pattern across the EEG electrodes (when averaged, parts of these patterns form traditional ERPs). This HsMM-MVPA method has been successfully applied to a range of cognitive tasks including associative memory recognition, arithmetic retrieval, and classical short-term memory tasks (Anderson et al, 2018(Anderson et al, , 2016Portoles, Borst, & van Vugt, 2018;van Maanen, Portoles, & Borst, in press;Walsh et al, 2017;Zhang, Borst, Kass, & Anderson, 2017;Zhang, van Vugt, Borst, & Anderson, 2018;Zhang, Walsh, et al, 2018). In a recent validation study, it was found that HsMM-MVPA allows for zooming into processes identified with RT-based methods by finding a range of corresponding cognitive stages (Berberyan, van Maanen, van Rijn, & Borst, 2021).…”
Section: 1lexical Decision Taskmentioning
confidence: 99%